2018
DOI: 10.1016/j.jpag.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Urban-Rural Inequities in the Parental Attitudes and Beliefs Towards Human Papillomavirus Infection, Cervical Cancer, and Human Papillomavirus Vaccine in Mysore, India

Abstract: Rural parents might be reluctant to recommend behaviors that can help prevent HPV infection and cervical cancer such as HPV vaccination for their daughters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
2
16
0
1
Order By: Relevance
“…A total of 778 parents living in the urban area and 831 parents living in the rural areas of Mysore district participated in this study. Detailed description of the study procedures are available elsewhere [33]. In brief, 12 schools located in the urban area and 11 schools located in the rural area were selected based on probability proportionate-to-size sampling.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 778 parents living in the urban area and 831 parents living in the rural areas of Mysore district participated in this study. Detailed description of the study procedures are available elsewhere [33]. In brief, 12 schools located in the urban area and 11 schools located in the rural area were selected based on probability proportionate-to-size sampling.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…More than two-thirds (78.0%) of the parents were willing to vaccinate daughter with HPV vaccine. Details of the study participant characteristics are described elsewhere [33].…”
Section: Characteristics Of the Study Participantsmentioning
confidence: 99%
“…Study participants recruitment procedures are explained in detail elsewhere [ 33 , 37 ]. In brief, 12 schools in the urban area (five government, four private and three religious) and 11 schools in the rural areas (10 government and one private) of Mysore district were selected based on probability proportionate to size sampling.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was administered in Kannada , the local language, to assess factors affecting general vaccination and HPV vaccination in particular. A detailed description of the questionnaire is described elsewhere [ 33 , 34 , 37 ]. It included items such as “ Please indicate (to the best of your knowledge whether all your children have had the following recommended vaccinations ” to assess immunization for BCG, DPT3, OPV and MCV.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly 528,000 women are diagnosed with cervical cancer each year with nearly half of them deceased [12]. The authors suggest that nearly 80% of the cases are found in third world countries are lacking the resources to battle this number of deaths.…”
Section: The Historical Perspective Of Hpvmentioning
confidence: 99%